Нагляд і контроль в сфері господарської діяльності як засіб реалізації публічного інтересу - Сєров, С. Л.; Sierov, Serhii; Сєров, Сергій (Одеса : Гельветика, 2019)
Здійснення нагляду та контролю є одним з важливих заходів у реалізації завдань та функцій держави. Обґрунтовано, що тим нагляд і контроль ефективніше досягають своєї мети, чим чіткіше та ефективніше здійснюються зазначені функції та є досконалішим, прозорішим і зрозумілішим для всіх порядок їх виконання. Зроблено висновок про те, що нагляд та контроль з боку держави за господарською діяльністю включає, по-перше, здійснювані в інтересах забезпечення прав громадян спостереження за дотриманням господарюючими суб’єктами норм і приписів законодавства, правил та стандартів, якістю та безпечністю як виробленої продукції, наданих послуг, так і їх виробництва. По-друге, це виявлення, аналіз та встановлення причин виникнення відхилень від згаданих правил та стандартів. По-третє – розробка альтернатив щодо приведення об’єкта контролю з фактичного до бажаного стану, їх оцінка та вибір найкращої. Under the supervision it is expedient to understand observation of its object. Control is appropriate to consider as a set of functions, including supervision – observation. To determine the full, it is necessary to have a sufficient list, we turn to the system analysis. Based on its methodology, we introduce the concept of the desired and actual state of the object of supervision (control). Regarding their functions, it is observing the preservation of the desired state of the object of supervision (control), detecting deviations from this state, analyzing the causes of their occurrence, and developing measures for bringing the object to the desired state. A clear definition of supervision and control is one of the important conditions for its effective implementation, and therefore the realization of the tasks and functions of the state. In the presence of the developed theoretical and methodological basis of supervision and control, the optimal achievement of the purpose of supervision and control, successful implementation of the tasks and functions of the state is possible. A clear definition of supervision and control is one of the important conditions for its effective implementation, and therefore the realization of the tasks and functions of the state. In the presence of the developed theoretical and methodological basis of supervision and control, the optimal achievement of the purpose of supervision and control, successful implementation of the tasks and functions of the state is possible. Supervision and control by the state of economic activity includes, firstly, observation of compliance by economic entities with the norms and regulations of legislation, rules and standards, quality and safety of both produced products, services rendered and their production. Second, it identifies, analyzes and establishes the causes of deviations from the above rules and standards. Third, the quality and safety of products, services provided, and their production in accordance with the standards. Regarding the nature of control in the field, it is both managerial and legal, which are closely intertwined.
Сєров С. Л. Нагляд і контроль в сфері господарської діяльності як засіб реалізації публічного інтересу / С. Л. Сєров // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), І. В. Сафін (заст. голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". - Одеса : Видавничий дім «Гельветика», 2019. - № 1. – C. 118 – 130
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; якість та безпечність продукції; качество и безопасность продукции; quality and safety of products; supervision